Amendment of the Instrument to Establish the SCA-1/Deferred Charges Administered Account : Extension of Termination Date. (Policy Papers; Policy Paper ;, 2011)
To help fulfill its purposes, the International Monetary Fund (the 'Fund') has adopted this Instrument to establish the SCA-1/Deferred Charges Administered Account in accordance with Article V, Section 2(b) (the 'Account'), which shall be governed and administered by the Fund in accordance with the terms and conditions of this Instrument.